Final report FLD Grant, May 1982-November 1984 to the Federal Livestock Department and Livestock Production Unit of the Federal Government of Nigeria - International Livestock Centre for Africa (International Livestock Centre for Africa, 1985)
Report showing 2 years of ILCA's activities in the humid zones of West Africa; stresses on the productivity of sheep & goats and trypanotolerant cattle production in the area; discusses the establishment of the first alley farming to alleviate nutritional stress of animals, and the first workshop on small ruminant production systems.